Magnesium and its alloys as degradable biomaterials : Corrosion studies using potentiodynamic and EIS electrochemical techniques - Müller, Wolf Dieter (2007)
Magnesium is potentially useful for orthopaedic and cardiovascular applications. However, the corrosion rate of this metal is so high that its degradation occurs before the end of the healing process. In industrial media the behaviour of several magnesium alloys have been probed to be better than magnesium performance. However, the information related to their corrosion behaviour in biological media is insufficient. The aim of this work is to study the influence of the components of organic fluids on the corrosion behaviour of Mg and AZ31 and LAE442 alloys using potentiodynamic, potentiostatic and EIS techniques. Results showed localized attack in chloride containing media. The breakdown potential decreased when chloride concentration increased. The potential range of the passivation region was extended in the presence of albumin. EIS measurements showed that the corrosion behaviour of the AZ31 was very different from that of LAE442 alloy in chloride solutions.